AN ANALYSIS OF LEARNING AUTONOMY OF THE SIXTH SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM UNIVERSITAS RIAU - Khairanisyah, Afifah; Erni, Erni; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aimed to know the learning autonomy of the sixth semester students of the English study program Universitas Riau. This research is quantitative research. The research involved 74 students from two classes. The instrument in this research is questionnaire. The questionnaire that researcher adapt is called MILLA (Measuring Instrument for Language Learner Autonomy) was designed by Carol. The result of the research reveals the results of the questionnaire analysis showed that 11 students 81% - 91% in the very high level, most of students 61% - 79% (57 of the students) in the high level, 5 students 43%-46% in the moderate level and 1 students 39% in the very low level. So, most of the students is high in learning autonomy.Key Word: Learning Autonomy